Pengaruh Faktor Lokasi, Kelengkapan Produk, Harga Dan Promosi Terhadap Pembelian Ulang Konsumen (Studi Kasus Pada Konsumen Tiara Toserba Desa Banjarwati Kecamatan Paciran Kabupaten Lamongan) - Nasruddin Nasruddin; Achmad Agus Prioyono; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT The purpose of this research is to know whether the location factor, product completeness, price and promotion to the repurchase of consumers (case study on the consumer Tiara Toserba Banjarwati Village, Paciran subdistrict, Lamongan Regency), which is located on Jl. Sunan Drajat No. 393. Independent variables: Location factors, product completeness, pricing and promotions. Dependent variables: consumer repurchase. The samples used in this study were 90 respondents who had re-purchased in Tiara Toserba with the Maholtra formula (the number of items of the declaration at five or X 5). Data source and method of collecting data by collecting primary or scale data of Likert by rounding out questionnaires. Analysis of the data used includes validity and reliability tests, test normality, classical assumption tests, multiple linear regression tests, hypothesized testing, and coefficient of determination testing with the help of SPSS 26 Software.The results showed that the variable location factor, product completeness, price and promotion simultaneously had significant effect on the repurchase of consumers in Tiara Toserba. As for the partial location factor variables, completeness of the product, prices have significant effect on the repurchase of consumers in Tiara Toserba. However, partial promotions have no significant effect on rebuying consumers in Tiara Toserba. Keywords: location factors, product completeness, price, promotion, consumer repurchase